2013
DOI: 10.1007/s11064-013-1076-2
|View full text |Cite
|
Sign up to set email alerts
|

Increased Noradrenaline Levels in the Rostral Pons can be Reversed by M1 Antagonist in a Rat Model of Post-traumatic Stress Disorder

Abstract: The dysregulation of hypothalamic-pituitary-adrenal axis and noradrenergic, serotonergic and glutamatergic systems are thought to be involved in the pathophysiology of post-traumatic stress disorder. The effect of selective M1 muscarinic receptor antagonist, pirenzepine on anxiety indices was investigated by using elevated plus maze, following exposure to trauma reminder. Upon receiving the approval of ethics committee, Sprague-Dawley rats were exposed to dirty cat litter (trauma) for 10 min and 1 week later, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 51 publications
1
13
0
Order By: Relevance
“…The first part of our study demonstrates that cat litter scent induced stress and resulted in higher cumulative freezing times and lower number of entries into the open arms of elevated plus maze in the stressed rats without prazosin injections. This finding is in accordance with the findings of the previous studies published from our laboratory [11,21]. On the other hand prazosin injections did not produce any significant difference in the total time spent on the open arms neither due to stress exposure nor due to treatments on the elevated plus maze.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The first part of our study demonstrates that cat litter scent induced stress and resulted in higher cumulative freezing times and lower number of entries into the open arms of elevated plus maze in the stressed rats without prazosin injections. This finding is in accordance with the findings of the previous studies published from our laboratory [11,21]. On the other hand prazosin injections did not produce any significant difference in the total time spent on the open arms neither due to stress exposure nor due to treatments on the elevated plus maze.…”
Section: Discussionsupporting
confidence: 93%
“…Stressful stimuli of many types produce marked increases in brain noradrenergic function. In an experimental study performed in rats using predator scent test that serves as an experimental model for PTSD, it was stated that NA levels increase in locus coeruleus (LC) in stressed rats [11]. The brain noradrenergic system is involved in mediating the fear conditioning [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…We used a systemic ( ip ) injection of pirenzepine to maintain the same route of administration for all drugs, which also ensured a minimally invasive method. Although pirenzepine presents low liposolubility, previous studies demonstrated that it crosses the blood brain barrier, reaches the central nervous system (11), and produces central effects (12,13).…”
Section: Methodsmentioning
confidence: 99%
“…Our previous another data showed that noradrenaline (NA) content in the rostral pons increased in traumatized rats with cat litter and this increase may serve as an additional neurochemical evidence for the model. Pirenzepine suppressed the anxiety index but it was not that effective in decreasing the prolonged freezing times [18].…”
mentioning
confidence: 88%
“…Our previous another data showed that noradrenaline (NA) content in the rostral pons increased in traumatized rats with cat litter and this increase may serve as an additional neurochemical evidence for the model. Pirenzepine suppressed the anxiety index but it was not that effective in decreasing the prolonged freezing times [18].In this current study, we wanted to demonstrate the ratio between proapoptotic and antiapoptotic proteins in the dorsal hippocampus, the amygdaloid complex and the frontal cortex of female rats traumatized with cat litter. The effects of fluoxetine or propranolol on behavioral parameters and neuronal apoptosis were also investigated.…”
mentioning
confidence: 92%